2016
DOI: 10.48550/arxiv.1609.04344
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-existence theorems on infinite order corks

Abstract: Suppose that X, X ′ are simply connected closed exotic 4manifolds. It is well-known that X ′ is obtained by an order 2 cork twist of X. We show that in the case of infinite order cork, this existence theorem does not always hold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…More recently, Tange has posted papers extending the methods of this article to exhibit n-fold boundary sums of our Z-corks as Z n -corks [21] and providing constraints on families of manifolds that can be related by Z-corks [20].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Tange has posted papers extending the methods of this article to exhibit n-fold boundary sums of our Z-corks as Z n -corks [21] and providing constraints on families of manifolds that can be related by Z-corks [20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently higher order corks ( [36], [14]) and surprisingly infinite order corks ( [23], see also [3], [24], [38]) were discovered, but interestingly Tange [37] showed that a natural extension of the above cork theorem does not always hold for an infinite exotic family, by showing a certain finiteness for Ozsváth-Szabó invariants of cork twisted 4-manifolds. More precisely, he gave infinite families of pairwise exotic closed 4-manifolds such that, for any 4-manifold X, any contractible submanifold W , and any self-diffeomorphism f of ∂W , the families cannot be constructed from X by twisting W via powers of f .…”
Section: Introductionmentioning
confidence: 99%
“…To address infinite lists X i (i ∈ Z) of 4-manifolds homeomorphic to X, such as an enumeration of all the exotic smooth structures on X, it is tempting to search for a single infinite cork (C, h) embedded in X such that X C,h i ∼ = X i for all i (here and below, ∼ = denotes diffeomorphism). Such a cork need not exist, however, as noted by Tange [25]. For example, it follows from the adjunction inequality that knot surgeries on the Kummer surface using any list of knots with unbounded Alexander polynomial degrees cannot be the cork twists associated to a fixed embedding of a single infinite cork (cf.…”
Section: Introductionmentioning
confidence: 99%